2021
DOI: 10.33730/2077-4893.3.2021.240323
|View full text |Cite
|
Sign up to set email alerts
|

Variability in 1000 kernel weight of winter bread wheat (Triticum aestivum L.) genotypes depending on ecological and agrotechnical factors

Abstract: In the ecological conditions of the central part of the Ukrainian Forest-Steppe (The V. M. Remeslo Myronivka Institute of Wheat, NAAS of Ukraine) the influence of growing season conditions (2016-17–2018-19), sowing dates (September 26, October 5, October 16) and different preceding crops (green manure, mustard, soybean, sunflower, corn) on variability of 1000 kernel weight of seventeen modern genotypes of winter wheat was investigated. Under environments of the central part of the Ukrainian Forest-Steppe, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
1
Order By: Relevance
“…On the first appropriate date, the plants were not exposed to heat stress during the grain filling period, so the metabolism processes increased Photosynthesis and the products of physiological construction processes, which increased the deposition of starch in the grains during the filling period at the expense of protein. These results agreed with [57,58]. who showed that the delay in planting date affects the quality and quantity of wheat yield as it reduces grain yield and increases the protein content in grains, as [59].…”
Section: Grain Yield (Ton Ha -1 )supporting
confidence: 90%
“…On the first appropriate date, the plants were not exposed to heat stress during the grain filling period, so the metabolism processes increased Photosynthesis and the products of physiological construction processes, which increased the deposition of starch in the grains during the filling period at the expense of protein. These results agreed with [57,58]. who showed that the delay in planting date affects the quality and quantity of wheat yield as it reduces grain yield and increases the protein content in grains, as [59].…”
Section: Grain Yield (Ton Ha -1 )supporting
confidence: 90%
“…Слід зазначити, що за стабільності посівних площ пшениці озимої основним шляхом збільшення валових зборів зерна є зростання врожайності. Підвищення продуктивності сільськогосподарських культур з урахуванням сучасних умов ведення аграрного виробництва є важливою проблемою землеробства [1,2].…”
unclassified